The Impact of Strategic Entrepreneurship on Sustainable Competitive Advantage: A Field Research in Egypt’s Petrochemicals and Energy Sector - Arabi, Nahla G.A.; Ahmed, Noha Khalifa Seddig (International Review of Management and Marketing, 2024)
The purpose of this research is to examine the impact of the strategic entrepreneurship, on sustainable competitive advantage in Egyptian’s petrochemicals and energy sector. The study adopts the quantitative approach specifically for the verification of hypotheses, by using the questionnaire to collect data from a sample of 500 senior managers. The results reveal that there is a statistically significant correlation between the five variables strategic entrepreneurship under study, namely: continuous innovation, Opportunity-Based Mindset, Proactive Behavior, Risk Taking, Value Creation, and sustainable competitive advantage, as the correlation coefficient recorded a significant positive correlation between strategic entrepreneurship and sustainable competitive advantage, as it amounted to (0.687**). According to multiple regression analysis, the researchers found that value creation capabilities has a strong predictive value for competitive advantage and continuous innovation has the lowest predictive value, accordingly the study recommends that a more effective policy for enhancing strategic entrepreneurship generally and continuous innovation specifically should be formulated in Egyptian’s petrochemicals and energy sector.